Lipid metabolism and osteonecrosis: unraveling causal mechanisms via multi-omics and mendelian randomization - Chen, Ying; Zhou, Zihong; Che, Hui; Li, Ding (Frontiers in Physiology, 2025)
Osteonecrosis (ON), a debilitating condition marked by ischemic bone death, has been clinically linked to dysregulated lipid metabolism, yet the causal relationships and underlying genetic mechanisms remain poorly defined. This study employed bidirectional Mendelian randomization (MR) analyses using genome-wide association study (GWAS) datasets to investigate causal effects between 179 plasma lipid species and ON. Functional enrichment and protein-protein interaction (PPI) analyses were conducted to identify key genes, followed by transcriptomic validation using public datasets and experimental confirmation through qRT-PCR and immunohistochemistry. MR analysis revealed that four lipid species had protective effects against ON, while two were associated with increased risk. Conversely, ON itself was found to induce a significant “lipid storm,” elevating 25 circulating lipid species, including phosphatidylcholines and triacylglycerols. PPI network analysis identified key regulatory hubs, with transcriptomic and experimental validation confirming significant dysregulation of APOE, PRKCA and ALK in osteonecrotic cartilage. These findings establish a bidirectional causal link between lipid dysregulation and ON and highlight novel molecular targets that may inform future therapeutic strategies.